2019
DOI: 10.23880/oajds-16000214
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Dental Anxiety and Fear in Children by using Camouflaged Syringe and Conventional Syringe

Abstract: Introduction: Dental Fear (DF) and Dental Anxiety (DA) are the terms, used to symbolize early signs of Dental Phobia (DP). Dental anxiety in children due to sight of injection is the most common. Local anesthesia technique using camouflaged syringes has been tried to decrease anxiety and fear in children. This study was conducted by using most reliable scale is Venham Picture Test (VPT) and Face, Leg, Activity, Cry and Constability (FLACC) Behavioral Pain Assessment Scale to assess anxiety and fear in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
1
1
Order By: Relevance
“…In contrast to our findings, previous studies have reported that using a camouflaged syringe significantly reduced dental anxiety [8,14,15]. This can be attributed to the fact that, in the previous studies, only children with no prior experience with dental injection and anesthesia were included.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, previous studies have reported that using a camouflaged syringe significantly reduced dental anxiety [8,14,15]. This can be attributed to the fact that, in the previous studies, only children with no prior experience with dental injection and anesthesia were included.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings demonstrated a statistically significant difference when using a camouflaged dental syringe. This is consistent with Monika et al, who reported better behavior when the camouflaged syringe was used [7,14,18].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation